(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to identify the sports talents of eighth-grade students at SMP Negeri 22, Jambi City, and to map sports that suit their potential. This study used a quantitative research design with a survey method. The study population was all 215 eighth-grade students. Through random sampling techniques, a sample of 15% of the population, or 28 students, was determined. The results showed that there were 17 students who had potential or talent in sports. The findings also confirmed that around 13 years of age is a more appropriate age limit for identifying sports talent, because ages 6–12 are still in the childhood phase, which is the initial stage of introduction to physical activity and sports. Overall, this study concluded that eighth-grade students at SMP Negeri 22, Jambi City, have a tendency to be talented in seven sports, namely football, volleyball, race walking, sepak takraw, gymnastics, table tennis, and boxing. These results can be a basis for schools in developing more targeted sports achievement coaching and development programs that are in accordance with students’ potential.